Epidemiological profile of sports injuries in athletes of the badminton selection of Teresina-PI (Research, Society and Development, 2021)
The objective is to investigate the main origins by Badminton athletes, how they manifest themselves and the impact on the athlete's performance. This is an observational, quantitative research, carried out in a sports club, from September to October 2020, after approval by the Ethics Committee of the UNIFACID University Center, under the number of opinions 4,276,525. Badminton athletes were included, with at least 1 year of practice in the sport. The data were collected through the electronic questionnaire (Google Forms). The data were analyzed using SPSS 20.0, followed by the Kolmogorov-Smirnov test, p